A Dual Mediation Model of Turnover Intention among Nurses: Evidence from Work-Related and Organizational Factors - Anah Furyanah; Cucu Sulastri (Journal of Advanced Research in Social Sciences and Humanities, 2023)
Aim: In addition to examining the mediating impacts of organizational commitment and The Joy of Working as a Nurse. This study examines the effects of workload, job stress, and work-life balance on nurses’ intentions to quit their positions. Methodology: This survey involved 194 nurses from Category C hospitals in Surabaya, Indonesia, with a total of 130 replies. Convenience sampling was the method employed, with a maximum quota established for each facility. Consequently, A final total sample of 130 people responded to the survey. Findings: The computation analysis’s findings demonstrate that job satisfaction, workload, and stress all positively but marginally influence turnover intention. Job satisfaction is positively but marginally impacted by job stress. Workload has a slight but positive impact on turnover intention. The results of the mediation show that workload and intention to leave cannot be mediated by the relationship between job stress and job satisfaction. According to the study’s findings, severe stress and burden would lower job satisfaction but won’t be able to considerably lower the intention to leave. Furthermore, the analysis’s findings demonstrate that organizational commitment significantly reduces turnover intention, Organizational commitment is strongly and positively influenced by quality of work life, while turnover intentions are negatively but not significantly influenced. This suggests that the relationship between nurses’ turnover intentions and quality of work life is somewhat mediated by organizational commitment. Implications/Novel Contribution: Not only filled the prominent research gap in novel setting, the study brings key policy recommendations and future research directions for scholars in the field.